EFFORTS TO IMPROVE THE QUALITY OF HUMAN RESOURCES (HR) AND COMMUNITY EMPOWERMENT THROUGH KKM-UNIBA 2022 IN GIRIJAYA VILLAGE, SAKETI DISTRICT, PANDEGLANG REGENCY: UPAYA MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA (SDM) DAN PEMBERDAYAAN MASYARAKAT MELALUI KKM-UNIBA 2022 DI DESA GIRIJAYA KECAMATAN SAKETI KABUPATEN PANDEGLANG - Pramudi Harsono; Saefullah Saefullah; Erik Sumantri; Nurmalasari Nurmalasari; Sindi Triyani (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
The quality of improving Human Resources through community empowerment (empowerment) is two different sides but the same purpose is to be effective with increasing results. Based on Law No.12 of 2012, higher education has defined the level of education after secondary education from diploma programs to specialist programs organized by higher education based on Indonesian basga culture. The existence of Student Work Lectures (KKM) by the Ministry of Education and Culture, it is hoped that students are required to carry out the Tri Dharma of Higher Education, namely education, research and community service. So it is hoped that students will become qualified and characterful individuals. KKM itself is a place to test and forge development to be multidisciplinary and have an entrepreneurial spirit (entreprenuership), which is useful for the community and also problems that exist in global problems that will later give a good name to universities. As was done by KKM-UNIBA 2022 students in group 59 in Girijaya Village, Saketi district, Pandeglang regency. What is the contribution and input to improve the quality of human resources through efforts to increase the quality of human resources and community empowerment